The effect of maximal- and explosive-strength training on performance indicators in cyclists - Beattie, K.; Carson, B. P.; Lyons, M.; Kenny, I. C. (International Journal of Sports Physiology and Performance, 2017)
Cycling economy (CE), power output at maximal oxygen uptake (WV.O2max), and anaerobic function (ie, sprinting ability) are considered the best physiological performance indicators in elite road cyclists. In addition to cardiovascular function, these physiological indicators are partly dictated by neuromuscular factors. One technique to improve neuromuscular function in athletes is through strength training. The aim of this study was to investigate the effect of a 20-wk maximal- and explosive-strength-training intervention on strength (maximal strength, explosive strength, and bike-specific explosive strength), WV.O2max, CE, and body composition (body mass, fat and lean mass) in cyclists. Fifteen competitive road cyclists were divided into an intervention group (endurance training and strength training: n = 6; age, 38.0 ± 10.2 y; weight, 69.1 ± 3.6 kg; height, 1.77 ± 0.04 m) and a control group (endurance training only: n = 9; age, 34.8 ± 8.5 y; weight, 72.5 ± 7.2 kg; height, 1.78 ± 0.05 m). The intervention group strength-trained for 20 wk. Each participant completed 3 assessments: physiology (CE, WV.O2max, power at 2 and 4 mmol/L blood lactate), strength (isometric midthigh pull, squat-jump height, and 6-s bike-sprint peak power), and body composition (body mass, fat mass, overall leanness, and leg leanness). The results showed significant between- and within-group changes in the intervention group for maximal strength, bike-specific explosive strength, absolute V.O2max, body mass, overall leanness, and leg leanness at wk 20 (P < .05). The control group showed no significant within-group changes in measures of strength, physiology, or body composition. This study demonstrates that 20 wk of strength training can significantly improve maximal strength, bike-specific explosive strength, and absolute WV.O2max in competitive road cyclists.